Pelatihan Pembuatan Video Pembelajaran Kreatif dan Inovatif di Masa Pandemi Covid 19 Pada SMP N 2 Karanganyar Demak - Nanik Susanti; Yudie Irawan; Wiwit Agus Triyanto (Universitas Muria Kudus, 2022)
The COVID-19 pandemic has brought changes to all sectors, including the education sector. The policy of learning from home in the midst of the Covid-19 pandemic has been carried out by schools in Indonesia. This policy is based on the Circular of the Minister of Education and Culture No. 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period for the Spread of Covid-19. One of the contents of the SE is to provide an appeal to learn from home through online learning or distance learning. Like other schools, during this pandemic, SMP N 2 Karanganyar Demak is required to be able to organize distance learning that is good, easy to understand and not boring. Judging from the conditions in the field, there are still many teachers who have limitations in terms of access and use of existing technology. Because the material distributed in the form of presentation files and e-books requires a deeper explanation, learning videos are seen as the right solution. The effect of using video media in learning is very high because the more often teachers use learning videos, the stronger/higher the impact on student learning outcomes will be. Learning video training at SMP N 2 Karanganyar utilizes the Camtasia application which functions to record and edit recordings. Teachers are required to make learning videos according to the subjects they teach.